Importance of representative metallurgical sampling and testwork programmes to reduce project risk – a gold case study. Issue 4 (2nd October 2019) - Dominy, Simon C.; O'Connor, Louisa; Purevgerel, Saranchimeg
ABSTRACT: When developing a process flowsheet, the risks in achieving positive financial outcomes are minimised by ensuring representative metallurgical samples and quality testwork. A case study is presented based on an underground gold operation, where poor metallurgical sampling led to grade and recovery underperformance. Sampling-related issues included: poor liaison between geologists and metallurgists; poor domaining; too few metallurgical samples collected and tested; unrepresentative sample composites and sub-samples; poor laboratory practice; and a lack of documentation and QAQC. These issues led to disruption over four years and are estimated to have cost around US115M in lost revenue and US7.5M in corrective expenditure. After an initial characterisation programme, a variability mini-bulk sampling and testwork phase was undertaken. This was followed by a pilot programme, progressing to trial mining and production. The paper emphasises the need for fit for purpose metallurgical sampling and testwork, and the early application of variability sampling.